LEGAL MEASURES TO CONTROL FOR DIETARY SUPPLEMENT PRODUCTS ADVERTISING ACCORDING fOOD ACT B.E. 2522 - Chinnehanha, Warunrak (Journal of MCU Nakhondhat, 2023)
The objectives of this research paper were: 1) Analyze the problem of legal measures in controlling the advertisement of food supplement products in Thailand. 2) Comparative study of legal measures controlling food supplement advertising in Thailand and other countries. 3) Suggest ways to improve the law for dietary supplement advertising to be more effective. This research is a documentary research. by studying and researching from relevant documents The results showed that It was found that dietary supplements are now very popular in Thailand. There are various sales channels. such as advertising for sale through online channels Posting notices by persuading consumers to be interested in advertising products is defined in the Food Act B.E. 2522, section 40 that “No one shall advertise quality benefits. or false properties of food or to deceive unreasonable beliefs” Any violation of such provisions shall be punished according to Section 70, which is imprisonment for a term not exceeding three years or a fine not exceeding thirty thousand baht or both which the provisions in Section 40 do not yet cover It is not appropriate and in line with the current problem situation. And in order to comply with the Act under the supervision of the Food and Drug Administration, the same criteria must be used to control the advertisement of food industry products. And the punishment under Section 70 is too light. Because nowadays the economy has changed. The offender receives more compensation than the punishment he or she has to receive, resulting in no intimidation, deterrence, or recklessness. and may lead to repeat offences.